Kepemimpinan Gereja dan Pengembangan Pelayanan di Era Digital: Menjawab Tantangan AI dan Society 5.0 di PGPI Langkat - Heryanto Heryanto; Rudy Butar-butar (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
This community service activity aims to improve digital literacy, understanding of artificial intelligence (AI), and the capacity of church leadership in addressing ministry challenges in the Society 5.0 era. The study applies a qualitative approach using a case study design and Participatory Action Research (PAR) through seminars, observations, documentation, and participatory discussions. The participants consisted of 61 individuals from various church denominations in Lalat Regency. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The results indicate an improvement in participants’ digital literacy understanding, reaching 62.3%, along with a strong commitment to the utilization of technology in ministry activities, reaching 86.9%. The seminar also highlighted the importance of adaptive, ethical, and biblically based leadership in responding to rapid technological changes. In addition, participants showed increased awareness of the role of artificial intelligence in supporting church services and administrative efficiency. The activity further demonstrated that collaborative learning and participatory engagement significantly enhance participants’ readiness to face digital transformation challenges. In conclusion, strengthening digital literacy and AI understanding is a crucial strategy for building a relevant, inclusive, and sustainable church in the digital era